The fine structure of the spermatheca in Anopheles aquasalis (Diptera: Culicidae) - Pascini, T. V.; Ramalho-Ortigão, Marcelo; Martins, G. F. (My University, 2013)
The vectorial capacity of mosquitoes is related to the reproductive output, and dependent on the ability of male spermatozoa to survive within the inseminated female. Mosquito females mate once, and immediately after mating, the male spermatozoa are transferred to and maintained in the ectodermic spermatheca. Mosquito spermathecae in culicines, especially of the yellowfever mosquito Aedes (Stegomyia) aegypti (L.), have been characterized in detail. In contrast, not much is known about this organ in anophelines. Here, the morphology of the spermatheca in the saltwater-tolerant mosquito Anopheles aquasalis Curry was investigated for the first time using a combination of light, confocal, and scanning and transmission electron microscopy. The spermatheca in An. aquasalis share many features with the three spermathecae present in Ae. aegypti, including a round-shaped reservoir and spermathecal duct glandular cells. However, differences such as the volume and cell types, as well as their numbers and distribution, were observed. The most remarkable difference seems to be the absence of a separated glandular unit as seen in Ae. aegypti. In An. aquasalis, the glandular cells are distributed along the reservoir wall, possibly representing a feature exclusive of anophelines. Together, these glandular cell units constitute the main secretory apparatus of An. aquasalis, and are the main source of secretions to nourish and maintain the viability of the gametes during the female's reproductive life span. Understanding the spermathecal organization and function will contribute to understand details of mosquito reproductive biology, and help answer questions related to the reproductive success of these major vectors of pathogens.
Citation: Pascini, T., Ramalho-Ortigao, J., & Martins, G. (2013). The Fine Structure of the Spermatheca in Anopheles aquasalis (Diptera: Culicidae). Annals of the Entomological Society of America, 106(6), 857–867. https://doi.org/10.1603/AN13079
Keywords: Anopheles; Mosquito; Reproductive system; Spermatheca